Validity and reliability of the Arabic version of the revised illness perception questionnaire for patients with hypertension - Sameer Al-Ghamdi; Alhaytham Mohammed Al Muaddi; Nawaf Ali Alqahtani; Tamim Yahya Alhasoon; Abdulaziz Abdullah Basalem; Abdulrahman Abdullah Altamimi (Frontiers Media S.A., 2022)
BackgroundHypertension is one of the leading causes of morbidity and mortality in Saudi Arabia affecting 31.4% of the population. The Illness Perception Questionnaire-Revised (IPQ-R) is a validated and reliable tool for assessing the perception of hypertension among patients. This cross-sectional study aimed to translate the Revised Illness Perception Questionnaire (IPQ-R) into Arabic and validate it among Arabic patients with hypertension from the outpatient departments of the Prince Sattam University Hospital and King Khalid Hospital (KKH) in Al-Kharj City in the Kingdom of Saudi Arabia.MethodsA bilingual panel of doctors and medical translators was assembled to translate the IPQ-R into Arabic. The questionnaire was administered to 100 adult Arabic speaking patients with clinically diagnosed primary hypertension. Patients with secondary hypertension or complications of hypertension were excluded from the study.ResultsFifty-seven patients (57%) were male and sixty-five (65%) were older than 40 years. Headache was the most common symptom of hypertension reported by 65% of the participants. The internal consistency of the questionnaire excluding the domain of 'Disease Identity' was 0.76 indicating satisfactory consistency. There were weak to moderate positive linear correlations (r = 0.003-0.561) between the domains of IPQ-R suggesting a reasonable discriminant validity among the domains.ConclusionThe Arabic version of the IPQ-R for hypertensive patients is a consistent, valid, and reliable tool to be used by researchers or clinicians for assessing knowledge, beliefs, and attitudes of Arabic speaking patients with hypertension living in Saudi Arabia.